Correlation Between Body Weight and Carcass Weight in the Selection of Village Chicken Three-Generation - Avrilliani, Puspita; Wiyanto, Eko; Erina, Silvia; Depison, Depison (Jurnal Sain Peternakan Indonesia, 2024)
This study aims to estimate the correlation between body weight and carcass weight in selected native chickens in the third generation (G3). The material used in this study was 200 DOC managed with a free-range system. The samples used to obtain carcass weight were determined by purposive sampling, consisting of 38 male chickens and 26 female chickens. The data obtained were analyzed using correlation and regression analysis. The observed variables were body weight (BW) at 2, 4, 6, 8, and 10 weeks of age (independent variable) and carcass weight (CW) at 10 weeks of age (dependent variable). The results showed that the average body weight (BW) of male and female chickens up to 6 weeks of age showed no significant difference (P>0.05). After eight weeks of age, the male free-range body weights were significantly different (P<0.05) higher than female chickens, while at the period of 10 weeks, the body weights of male chickens were significantly different (P<0.01) and showed higher than female chickens. Male chickens' average free-range carcass weight was significantly higher (P<0.01) than the carcass weight (CW) of female chickens. The correlation between body weight at 2, 4, 6, 8, and 10 weeks and carcass weight showed a close correlation, ranging from 0.71 to 0.97. The highest correlation coefficient values were found in male and female native chickens at ten weeks of age, with 0.94 and 0.97. It can be concluded that BW at 2, 4, 6, 8, and 10 weeks of age in male and female chickens strongly correlated with carcass weight (CW). Hence, body weight (BW) could be used as a selection criterion to increase chickens' carcass weight (CW) under study.